Integration of a Geriatric Assessment With Intervention in the Care of Older Adults With Hematologic Malignancies - Wall, Sarah A.; Huang, Ying; Keiter, Ashleigh; Funderburg, Allesia; Kloock, Colin; Yuhasz, Nicholas; Gure, Tanya R.; Folefac, Edmund; Stevens, Erin; Presley, Carolyn J.; Williams, Nicole O.; Krok-Schoen, Jessica L.; et al. (Frontiers in Oncology, 2021)
The incidence of hematologic malignancies (HMs) is highest in the seventh decade of life and coincides with increasing occult, age-related vulnerabilities. Identification of frailty is useful in prognostication and treatment decision-making for older adults with HMs. This real-world analysis describes 311 older adults with HMs evaluated in a multidisciplinary oncogeriatric clinic. The accumulation of geriatric conditions [1-unit increase, hazards ratio (HR) = 1.13, 95% CI 1.00–1.27, p = 0.04] and frailty assessed by the Rockwood Clinical Frailty Scale (CFS, mild/moderate/severe frailty vs. very fit/well, HR = 2.59, 95% CI 1.41–4.78, p = 0.002) were predictive of worse overall survival. In multivariate analysis, HM type [acute leukemia, HR = 3.84, 95% CI 1.60–9.22, p = 0.003; myelodysplastic syndrome (MDS)/myeloproliferative neoplasm (MPN)/bone marrow failure, HR = 2.65, 95% CI 1.10–6.35, p = 0.03], age (per 5-year increase, HR = 1.46, 95% CI 1.21–1.76, p < 0.001), hemoglobin (per 1 g/dl decrease, HR = 1.21, 95% CI 1.05–1.40, p = 0.009), deficit in activities of daily living (HR = 2.20, 95% CI 1.11–4.34, p = 0.02), and Mini Nutrition Assessment score (at-risk of malnutrition vs. normal, HR = 2.00, 95% CI 1.07–3.73, p = 0.03) were independently associated with risk of death. The most commonly prescribed geriatric interventions were in the domains of audiology (56%) and pharmacy (54%). The Rockwood CFS correlated with prescribed interventions in nutrition (p = 0.01) and physical function (p < 0.001) domains. Geriatric assessment with geriatric intervention can be practically integrated into the routine care of older adults with HMs.